Beyond the Map: Enamel Distribution Characterized from 3D Dental Topography - Thiery, Ghislain; Lazzari, Vincent; Ramdarshan, Anusha; Guy, Franck (Frontiers in Physiology, 2017)
Enamel thickness is highly susceptible to natural selection because thick enamel may prevent tooth failure. Consequently, it has been suggested that primates consuming stress-limited food on a regular basis would have thick-enameled molars in comparison to primates consuming soft food. Furthermore, the spatial distribution of enamel over a single tooth crown is not homogeneous, and thick enamel is expected to be more unevenly distributed in durophagous primates. Still, a proper methodology to quantitatively characterize enamel 3D distribution and test this hypothesis is yet to be developed. Unworn to slightly worn upper second molars belonging to 32 species of anthropoid primates and corresponding to a wide range of diets were digitized using high resolution microcomputed tomography. In addition, their durophagous ability was scored from existing literature. 3D average and relative enamel thickness were computed based on the volumetric reconstruction of the enamel cap. Geometric estimates of their average and relative enamel-dentine distance were also computed using 3D dental topography. Both methods gave different estimations of average and relative enamel thickness. This study also introduces pachymetric profiles, a method inspired from traditional topography to graphically characterize thick enamel distribution. Pachymetric profiles and topographic maps of enamel-dentine distance are combined to assess the evenness of thick enamel distribution. Both pachymetric profiles and topographic maps indicate that thick enamel is not significantly more unevenly distributed in durophagous species, except in Cercopithecidae. In this family, durophagous species such as mangabeys are characterized by an uneven thick enamel and high pachymetric profile slopes at the average enamel thickness, whereas non-durophagous species such as colobine monkeys are not. These results indicate that the distribution of thick enamel follows different patterns across anthropoids. Primates might have developed different durophagous strategies to answer the selective pressure exerted by stress-limited food.